PHARMACEUTICO-ANALYTICAL STUDY OF MUKTA BHASMA PREPARED IN GODUGDHA - lata, Suman; S.Biradar, Rudrambika (International Journal of Ayurveda and Pharma Research, 2015)
Drug does its action on basis of its Rasa, Guna, Veerya, Vipaka (acc.to Ayurveda) and chemical composition (acc. to Modern concept) present in it. They are widely used in form of Bhasma, which is exclusively unique dosage form of Ayurveda, these acts in small doses and can cure chronic ailments. Mukta bhasma (calx of pearl) contains calcium carbonate and widely recommended and traditionally used for gastro-intestine tract disorders, anti-pyretic and it strengthens bones. The aim of study is Pharmaceutical and Analysis of Mukta Bhasma prepared in Godugdha by analytical procedures carried out vide infra in two major headings incorporating physico-chemical tests and advanced instrumental techniques like XRD and XRF. 300gms Raw Mukta was taken and gets 208gms dull white Mukta Bhasma. The Calcium percentage of Mukta Bhasma was 43.86% w/w by AAS and by XRF method Ca% in Mukta is 45.07%. Mukta Bhasma was evaluated for loss on drying (0.24%w/w), total ash (99.84%w/w), acid insoluble ash (0.34%w/w), water soluble ash (8.31%w/w), specific gravity (1.0185) and Particle size 20nm to 100nm by TEM was obtained. XRD peaks of the sample confirmed the presence of Calcium Carbonate (Calcite). Elements Detected by XRF study were present in Mukta Bhasma Ca (45.07%), O (41.52%), C (12.44%), Na (0.15%), P (0.13%), Si (0.12%), Cl (0.11%) S (0.08%), Mn (0.07%), Mg (0.07%), K (0.07), Sr (0.05%), Al (0.04%), Fe (0.04%), As (0.02%), Cu (0.01%), Zr in traces.